Percutaneous reduction of thoracolumbar fractures using monoaxial screws: Comparison of two instruments based on initial reduction and loss of reduction - Esra Aydin; Philipp Schenk; Arija Jacobi; Thomas Mendel; Friederike Klauke; Bernhard Wilhelm Ullrich (Brain and Spine)
Introduction: Percutaneous techniques for the surgical treatment of vertebral fractures are constantly progressing. There are different biomechanics involved. Research question: Two percutaneous, monoaxial fixation systems with different reduction tools were analyzed in relation to their reduction capacity. Additionally, the impact of anterior fusion, fracture severity and bone quality on reduction and loss of reduction were examined. Material and methods: 117 cases were retrospectively included in the monocentric study. The subsample (N = 53) with complete data at follow-up times was used to analyze the influence of anterior fusion. The dependencies on fracture severity and bone quality were determined using Spearman and Pearson correlation. Results: Both systems achieved equally good reduction (9° mean, 95%-CI: 8°–11°, p < 0.001). Anterior fused patients showed not significant (p = 0.057) less loss of reduction over time. Fracture severity had neither an influence on reduction or loss of reduction. Bone quality was positively correlated with greater amount of reduction and less loss of reduction. Early reduction within two days correlated with a greater amount of reduction (p = 0.006). Screw diameters and the patient's weight had no influence on loss of reduction. Complications occurred only in “V2” group. Discussion and conclusion: Both systems are equivalent in reduction ability. The additional anterior fusion did not result in significantly lower reduction losses. The subsample being small, is a limitation. Good bone quality correlates with better initial reduction and less reduction loss. A preoperative bone density measurement can lead to optimization of surgical techniques.